IL-3 is essential for ICOS-L stabilization on mast cells, and sustains the IL-33-induced RORγt+ Treg generation via enhanced IL-6 induction - Drube, Sebastian; Müller, Sylvia; Weber, Franziska; Wegner, Philine; Böttcher-Loschinski, Romy; Gaestel, Matthias; Hutloff, Andreas; Kamradt, Thomas; Andreas, Nico (Immunology, 2021)
IL-33 is a member of the IL-1 family. By binding to its receptor ST2 (IL-33R) on mast cells, IL-33 induces the MyD88-dependent activation of the TAK1-IKK2 signalling module resulting in activation of the MAP kinases p38, JNK1/2 and ERK1/2, and of NFκB. Depending on the kinases activated in these pathways, the IL-33-induced signalling is essential for production of IL-6 or IL-2. This was shown to control the dichotomy between RORγt+ and Helios+ Tregs, respectively. SCF, the ligand of c-Kit (CD117), can enhance these effects. Here, we show that IL-3, another growth factor for mast cells, is essential for the expression of ICOS-L on BMMCs, and costimulation with IL-3 potentiated the IL-33-induced IL-6 production similar to SCF. In contrast to the enhanced IL-2 production by SCF-induced modulation of the IL-33 signalling, IL-3 blocked the production of IL-2. Consequently, IL-3 shifted the IL-33-induced Treg dichotomy towards RORγt+ Tregs at the expense of RORγt− Helios+ Tregs. However, ICOS-L expression was downregulated by IL-33. In line with that, ICOS-L did not play any important role in the Treg modulation by IL-3/IL-33-activated mast cells. These findings demonstrate that different from the mast cell growth factor SCF, IL-3 can alter the IL-33-induced and mast cell-dependent regulation of Treg subpopulations by modulating mast cell-derived cytokine profiles.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IL-3; IL-33; immune homeostasis; mast cells; T